The Right PREMTM: Rasch analysis of a new patient reported experience measure for use by older people in hospital - Louise Heuzenroeder (The Beryl Institute, 2021)
Healthcare rights exist to protect older people from harm and to empower older people to participate in their care with independence, choice and control. Multiple investigations revealing abuse provide evidence that older people’s rights are being breached. Older people must have the opportunity to report on their experience of care against their rights. The Right PREMTM is a new instrument designed to measure older people’s experience of care against their healthcare rights. The objective of this cross-sectional validation study was to assess the psychometric properties of a new instrument to measure the experience of care consistent with the healthcare rights of older people in the hospital setting. Data were collected from older people who were current hospital inpatients of medical wards in four South Australian metropolitan hospitals. The Rasch model was used to assess the psychometric properties of the patient version of The Right PREMTM. The analysis was performed using the Winsteps® software program. Two hundred older patients completed the 50-item questionnaire. During the process of analysis, four items were removed as they did not fit the model and a further 11 items were removed due to high residual correlations. The final 23 items had a Person Separation Index of 2.23, a Person Separation Reliability Coefficient 0.83, an Item Separation Index of 7.70 and an Item Separation Reliability Coefficient of 0.98. Rasch analysis of the patient version of The Right PREMTM, based on a robust sample, demonstrated this new instrument is psychometrically sound and warrants ongoing development. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.